Association between skin injuries and the importance atributed to prevention by health professionals during the pandemic - Euzeli da Silva Brandão; Regina Serrão Lanzillotti; Paula Dadalti Granja; Liliane Faria Silva; Maria Helena Sant'Ana Mandelbaum; Renato Tonole (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To verify the association between the occurrence of skin lesions due to the use of products and/or personal protective equipment and the importance attributed to preventive care among health professionals working on the front lines of the struggle against the COVID-19 pandemic. Method: Cross-sectional, analytical study, carried out between May and June 2020, with a convenience sample (n=398) of health workers from 10 professional categories. To verify the existence of an association between the occurrence of skin lesions and exposure variables, a Contingency Table was used to obtain the Prevalence Ratio and respective Confidence Intervals. Results: 260 (65.3%) participants self-declared the development of skin lesions, predominantly nurses (53.8%), women (54.0%), from public institutions (52.8%), characterized by pressure injuries (37.3%), contact/allergic dermatitis (25.8%), or both lesions simultaneously (16.5%). More than half of professionals (53.5%) used preventive products, mainly moisturizers (51.0%). Conclusion: There was probability of an association between professionals who attributed less importance to the predictor "Protocol for proper product PPE and products" and the risk of skin injuries.